Pengembangan Media Ular Tangga Berbasis Etnosains pada Mata Pelajaran IPAS Kelas IV di SDN 1 Mekarsari - Rizka Aulia; Mohammad Liwa Ilhamdi; Muhammad Syazali (Mataram University, 2026)
This study aims to assess the validity, practicality, and effectiveness of the developed ethoscience-based Snakes and Ladders game. The research method used was Research and Development (R&D) based on the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), with the research subjects being 29 fourth-grade students at SDN 1 Mekarsari. The results of this study indicate that the ethnoscience-based snakes and ladders game is highly valid, with a 95% agreement rate from subject matter experts and a 91% agreement rate from media experts. Regarding the practicality of the game, student response surveys in small groups yielded a score of 97.77%, while those in large groups scored 85.58%; teacher responses scored 95%, meeting the criteria for a very positive rating. The effectiveness of the media was demonstrated by an N-gain score of 0.76, with a percentage of 76.37%, which falls into the high category. Based on these results, it can be concluded that the ethnoscience-based snakes and ladders game developed is valid, practical, and effective for use in IPAS learning on the topic of forces around us.